Synthesis Characterisation and Reactions of Some Coordination Complexes of α,α’-Bipyridyl Involving Organotin Derivatives as Lewis Acids - Ahmad, Nihal; Srivastava, Sadhna (Asian Journal of Chemistry, 2012)
Some coordination complexes were prepared using α,α’-bipyridyl as Lewis bases and the organotin derivatives as Lewis acids. Some replacement reactions were also done using ethylenediamine, 1,10-phenanthroline and α,α’-bipyridyl as secondary ligands. These secondary ligands being better donors were found to replace the anion in order to order to coordinate with the Lewis acid. All these complexes were characterized on the basis of elemental analysis, IR and 1H NMR studies.